1998
DOI: 10.1063/1.477346
|View full text |Cite
|
Sign up to set email alerts
|

Resonant ion-dip infrared spectroscopy of the S4 and D2d water octamers in benzene-(water)8 and benzene2-(water)8

Abstract: Resonant ion-dip infrared spectroscopy of benzene-(water) 9 : Expanding the cube The techniques of resonant two-photon ionization ͑R2PI͒, UV-UV ͑ultraviolet͒ hole-burning, and resonant ion-dip infrared ͑RIDIR͒ spectroscopies have been employed along with density functional theory ͑DFT͒ calculations to assign and characterize the hydrogen-bonding topologies of two isomers each of the benzene-͑water) 8 and (benzene͒ 2 ͑water) 8 gas-phase clusters. The BW 8 isomers ͑Bϭbenzene, Wϭwater͒ have R2PI spectra which are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
140
0
3

Year Published

2001
2001
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(157 citation statements)
references
References 81 publications
14
140
0
3
Order By: Relevance
“…The parallel intensity decrease of the sub-band (3) should be interpreted in terms of an accompanying decrease in the fraction of acyclic tetramers (whose oscillator number in overall should decrease from 16 to eight, assuming that two clusters of the type shown in Figure 4 b must join together to form the structure presented in Figure 4 c). This assignment is also in good agreement with published data for the condensed-phase cubic octamer [53][54][55][56] or the planar cyclic tetramer fragments. [50][51][52] C) We suggest, for the first time, that the two kinds of dense structures that show up under ambient and high-pressure conditions are nothing else but alternative (high-density) forms of liquid water involved in multiple liquid-liquid transitions "above" the second critical point as hypothesized in the literature.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The parallel intensity decrease of the sub-band (3) should be interpreted in terms of an accompanying decrease in the fraction of acyclic tetramers (whose oscillator number in overall should decrease from 16 to eight, assuming that two clusters of the type shown in Figure 4 b must join together to form the structure presented in Figure 4 c). This assignment is also in good agreement with published data for the condensed-phase cubic octamer [53][54][55][56] or the planar cyclic tetramer fragments. [50][51][52] C) We suggest, for the first time, that the two kinds of dense structures that show up under ambient and high-pressure conditions are nothing else but alternative (high-density) forms of liquid water involved in multiple liquid-liquid transitions "above" the second critical point as hypothesized in the literature.…”
Section: Resultssupporting
confidence: 90%
“…Furthermore, these local heterogeneities (patches) should fit the "host" hexagonal structure at the maximal level of H-bonding connectivity. Among a large number of theoretically possible structures, [22][23][24][25] the planar tetramers [48][49][50][51][52] and a cubic octamer structure [53][54][55][56] seem to meet the above-mentioned requirements better (see ref. [19] for the previous conjecturing, Figure 4).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Crystal packing forces and hydrogen bonds between the water octamer and the surrounding molecular complexes make the solid phase much different from the gas-phase environment, stabilizing these three different forms of the water octamer. In the gas-phase IR spectroscopy and DFT calculations have shown that the D 2d and S 4 isomers are present in a cold molecular beam, a finding that is supported by the stability of these two cubic structures relative to every other octamer [59,68,71,72,114]. The G3 HF/6-31G* scaled frequency of 3,696 cm Ϫ1 for the free OH stretch of the D 2d isomer is in excellent agreement with the experimental free OH stretch observed in the gas-phase benzene-D 2d structure, which is 3,713 cm Ϫ1 [72].…”
Section: Day Kirschner and Shieldsmentioning
confidence: 98%
“…The solid-phase crystallographic studies of various molecules have uncovered octamers of water hydrogen-bonded with organic and inorganic complexes, including a C i cube [78], a distorted pseudo-S 4 octamer [101], and a cyclic structure [94]. In the gas-phase IR spectroscopy and density functional theory (DFT) calculations suggested that the D 2d and S 4 isomers were present [68,71], and these two species have been definitively identified associated with benzene molecules through a combination of spectroscopic methods and DFT calculations [72]. Most of the theoretical focus has been on the cubic structures, which have been observed in cold spectroscopic beams [68,71].…”
mentioning
confidence: 97%